Infiltrasi Tanah Pada Beberapa Penggunaan Lahan Di Sub DAS Kawatuna - Ahmad, Elvira; Naharuddin, Naharuddin; Rukmi, Rukmi (Mitra Sains, 2024)
The research was conducted in the Kawatuna Sub-watershed with the aim of studying the physical properties of the soil and knowing the infiltration rate of several land uses in the Kawatuna Sub-watershed. This study used the Horton equation formula and took soil samples for analysis at the Laboratory of Soil Science, Faculty of Agriculture, Tadulako University, Palu. The results showed that the physical properties of the soil greatly influenced the infiltration process, the highest organic matter was secondary soil 6.10%, dry land agriculture 4.50% and the lowest was shrubs 3.04%. Secondary forest soil textures are loam and dusty loam, dry land agriculture has sandy loam textures, and shrubs have loamy, sandy loam and dusty loam textures. In terms of physical properties of water content, dry land agriculture had the highest water content 21.48%, secondary forest 19.19% and shrubs the lowest 15.54%. The highest infiltration rate was secondary forest land (12.74 cm/hour) with fast criteria, dry land agriculture (7.80 cm/hour) medium fast category and shrub land (6.19 cm/hour) medium category.